Crime films - Leitch, Thomas M. (Genres in American cinema., 2002)
This book surveys the entire range of crime films, including important subgenres such as the gangster film, the private eye film, film noir, as well as the victim film, the erotic thriller, and the crime comedy. Focusing on ten films that span the range of the twentieth century, Thomas Leitch traces the transformation of the three leading figures that are common to all crime films: the criminal, the victim and the avenger. Analyzing how each of the subgenres establishes oppositions among its ritual antagonists, he shows how the distinctions among them become blurred throughout the course of the century. This blurring, Leitch maintains, reflects and fosters a deep social ambivalence towards crime and criminals, while the criminal, victim and avenger characters effectively map the shifting relations between subgenres, such as the erotic thriller and the police film, within the larger genre of crime film that informs them all.